PENDAMPINGAN PEMASARAN PRODUK HASIL HOME INDUSTRY BERBASIS MEDIA SOSIAL DALAM UPAYA MEMBERDAYAKAN IBU RUMAH TANGGA DI KABUPATEN PRINGSEWU - Fauzi Fauzi; Rita Irviani; Siti Mukodimah (Jurnal PkM Pemberdayaan Masyarakat, 2020)
The era of globalization and free market systems in which these conditions require speed, accuracy and effectiveness are certainly a challenge for home-based businesses to compete and continue to survive. The rapid flow of information technology development has an impact and potential that can be utilized in developing the business of home industry players to expand the reach of marketing through social media. This assistance was carried out to help the community, especially home industry players, identify the benefits of using social media in developing marketing products produced by home industries in the Pringsewu district. The subjects in this study were selected by purposive sampling involving 42 home industry players in Pringsewu District. The result of this assistance is that home industry players have the skills to innovate in marketing products through social media Facebook, Instagram, and Whatsapp that are trending and much loved by Indonesian people. The three media are the media with the most active users that are used as a means of utilizing promotional media using social media. Aside from being a promotional medium for home industry players can also identify consumer needs and see trends that can be used as a reference for variations and product updates. Social media is an appropriate tool that can be used as a reciprocal communication medium to respond to consumers and increase market share and sales volume.